EL SISTEMA DE FRANJA DE PRECIOS PARA LOS PRODUCTOS AGRÍCOLAS EN EL PACTO ANDINO: DEFINICION DE CAMBIO ESTRUCTURAL - Del Valle, Manuel (1996)
It analyzes the structural change in the context of the price band in the Andean Pact in order to advance proposals for the reform of Decision 37.1 so that it can consider the systematic and sustained changes in the international product market. The focus of the work is statistical, since the system is updated using moving averages and statistical criteria. Thirteen time series used in the price band system are analyzed and univariate models are proposed for each one of them. Furthermore, a rule is proposed to define the structural change, and the univariate models obtained are used to prove said rule using Monte Carlo test for the thirteen products. It is concluded that the price band system can be useful to face short-term fluctuations in international prices, as well as long-term adjustments, but it is not prepared to solve problems generated by structural changes, so it can be modified to consider this issue, but the basic principle of the system should be maintained.